MODEL PEMBERDAYAAN KEMITRAAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN (KSPP) SYARIAH MADANI JAWA TIMUR DALAM PENINGKATAN PENDAPATAN DAN KESEJAHTERAAN PENGELOLA UMKM DI TRENGGALEK - Melvin Sephia Febriarisca; Melisa Wahyu Fandyansari; Loesita Sari; Heru Sofian (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Micro-enterprises play an important role in developing the country's economy, especially the economy of the surrounding community to meet their daily needs, especially in the present and in the future. This study uses a qualitative approach to refer more deeply to the social situation under study. The results of this study are the Partnership Empowerment Model developed by KSPPS Madani East Java at this time, which is a pick-up system where the empowerment system implemented by cooperatives allows them to visit members' locations and provide routine assistance in saving, financing and increasing capital, as well as introducing products or new cooperative technologies.